Principles for scientists working at the river science‐policy interface. (20th February 2022) - Thompson, Ross M; Barbour, Emily J; Bradshaw, Corey J A; Briggs, Sue; Byron, Neil; Grace, Michael; Hart, Barry T.; King, Alison J.; Likens, Gene E.; Pollino, Carmel A.; Sheldon, Fran; Stewardson, Michael J; et al.
Abstract: In the face of mounting environmental and political challenges in river management, accurate and timely scientific information is required to inform policy development and guide effective management of waterways. The Murray–Darling Basin is Australia's largest river system by area and is the subject of a heavily contested series of water reforms relying comprehensively on river science. River scientists have specialised knowledge that is an important input into evidence‐based decision‐making for the management of the Murray–Darling Basin, but despite extensive literature on the interface between science and policy, there is little guidance on achieving policy relevance for practicing scientists. Here, we provide a set of important discussion points for water scientists to consider when engaging with policy‐makers and environmental water managers. We place our considerations in the context of a broader literature discussing the role of natural‐resource scientists engaging with policy and management. We then discuss the different roles for river scientists when engaging in this space, and the advantages and pitfalls of each. We illustrate the breadth of modes of engagement at the science‐policy‐management interface using the Murray–Darling Basin as an example. We emphasise the need for effective governance arrangements and data practices to protect scientists from accusations of operating as advocates when working to inform management and policy.